A porous thermal battery electrolyte sheet and a method of making the same

CN122659167BActive Publication Date: 2026-10-20CHINA ELECTRONIC TECH GRP CORP NO 18 RES INST
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611131237.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-29
Publication Date
2026-10-20
Estimated Expiration
2046-07-29

AI Technical Summary

Technical Problem

[0006]针对现有技术存在的不足,本发明提供一种通过碳酸镁造孔制备的多孔热电池电解质片及其制备方法,旨在解决传统热电池电解质孔隙率不可控、孔道连通性差、力学性能与离子传导性能难以兼顾、工艺流程繁琐等的技术问题,实现多孔电解质片的高效、可控、稳定制备,提升热电池整体电化学性能

Benefits of technology

1.孔结构可控性强:通过调控碳酸镁造孔剂的掺量与粒径,可精准控制电解质片孔隙率与孔径,形成连续连通孔道,优化离子传输路径,有效提升热电池激活速度与大倍率放电性能,降低电池内阻。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122659167B_ABST
    Figure CN122659167B_ABST
Patent Text Reader

Abstract

The application discloses a porous thermal battery electrolyte sheet and a preparation method thereof, and belongs to the technical field of thermal battery material preparation. The electrolyte sheet is prepared from a molten salt and an adsorbent as a base body, and 5-40% magnesium carbonate as a pore-forming agent, and is prepared through raw material pretreatment, powder mixing, dry pressing forming and stepwise temperature rising sintering. The electrolyte sheet has controllable porosity, uniform and connected pores, and good mechanical properties and ion conduction performance through controllable thermal decomposition of the pore-forming agent. The preparation process does not introduce impurities, is simple, is suitable for the existing production system, effectively solves the problems of uncontrollable porosity and performance imbalance of the traditional electrolyte, reduces the internal resistance of the thermal battery, and is suitable for industrialized batch production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of key material preparation technology for thermal batteries, specifically relating to a thermal battery electrolyte sheet, and more particularly to a method for preparing a porous thermal battery electrolyte sheet based on a solid-phase decomposable pore-forming agent. Background Technology

[0002] Thermal batteries, as high-temperature molten salt storage primary batteries, possess core advantages such as high discharge rate, wide operating temperature range, long storage life, and strong environmental adaptability, and are widely used in special power supply fields such as aerospace, military equipment, and emergency power. The electrolyte is the core functional component of the thermal battery, and its pore structure, ion conductivity, and mechanical stability directly determine the activation response speed, discharge performance, and service reliability of the thermal battery.

[0003] Existing traditional thermal battery electrolyte preparation processes mostly involve direct mixing of molten salt and adsorbent, high-temperature sintering, crushing and powdering, and powder pressing. Electrolyte sheets prepared by this process have problems such as disordered internal pores, poor pore connectivity, and inability to precisely control porosity, which leads to obstruction of molten salt ion transport paths, resulting in high internal resistance and slow activation speed under high-rate discharge conditions. Moreover, the traditional process is cumbersome, and multiple heat treatments and mechanical crushing can easily lead to material loss, which is not conducive to mass production.

[0004] Currently, there are many attempts in the industry to modify electrolyte pores. Existing technologies use spherical PMMA (polymethyl methacrylate) powder as a pore-forming agent to prepare porous electrolyte sheets for thermal batteries. However, PMMA easily produces organic vapors such as formaldehyde, formic acid, and MMA (methyl methacrylate) when decomposed at high temperatures, as well as gases such as H2O and trace amounts of carbon residue. This can seriously contaminate the electrolyte material and cause battery self-discharge. These conventional pore-forming processes easily introduce impurities, disrupt the original composition ratio of the electrolyte, and easily affect the electrolyte's ion conductivity and high-temperature stability, failing to meet the application requirements of high-performance thermal batteries.

[0005] To address the aforementioned issues, developing a porous electrolyte preparation method that is simple in process, has controllable pore structure, stable in performance, introduces no impurities, and is compatible with existing thermal battery electrolyte production systems has become a pressing technical problem to be solved in this field. Summary of the Invention

[0006] To address the shortcomings of existing technologies, this invention provides a porous thermal battery electrolyte sheet prepared by magnesium carbonate pore formation and its preparation method. It aims to solve the technical problems of uncontrollable porosity, poor pore connectivity, difficulty in balancing mechanical properties and ion conduction properties, and cumbersome process flow in traditional thermal battery electrolytes, thereby achieving efficient, controllable, and stable preparation of porous electrolyte sheets and improving the overall electrochemical performance of thermal batteries.

[0007] To achieve the above objectives, the present invention adopts the following technical solution: a porous thermal battery electrolyte sheet, comprising the following components: molten salt, adsorbent, and magnesium carbonate pore-forming agent, wherein the mass percentage of each component is as follows: Molten salt: 40%–60%; Adsorbent: 15%–45%; Magnesium carbonate pore-forming agent: 5%–40%; The electrolyte sheet has uniformly connected pores and channels inside.

[0008] Furthermore, the molten salt is one of the following: LiCl-KCl binary eutectic molten salt, LiF-LiCl-LiBr ternary eutectic molten salt, LiF-LiBr-KBr ternary eutectic molten salt, LiCl-LiBr-KBr ternary eutectic molten salt, LiF-NaF-KF ternary eutectic molten salt, LiCl-KCl-LiF ternary eutectic molten salt, or LiCl-KCl-CaCl2 ternary eutectic molten salt.

[0009] Furthermore, the adsorbent is active MgO or γ-Al2O3, and the powder particle size is 80-200 mesh.

[0010] Furthermore, the powder particle size of the magnesium carbonate pore-forming agent is ≤10μm.

[0011] A method for preparing the above-mentioned porous thermal battery electrolyte sheet includes the following steps: Step 1: Vacuum dry the molten salt, adsorbent, and magnesium carbonate pore-forming agent separately; Step 2: Weigh each powder after step 1 according to the ratio, mix them evenly to obtain a mixed powder; Step 3: The mixed powder is dry-pressed into shape to obtain electrolyte tablets; Step 4: Place the electrolyte sheet in an inert atmosphere and sinter it using a stepped heating process, then cool it to room temperature to obtain a porous thermal battery electrolyte sheet. The stepped heating system includes: First stage: Heat to the temperature at which the pore-forming agent completely decomposes, so that the pore-forming agent can fully decompose and produce gas, forming uniform and interconnected pore channels; Second stage: Continue heating to 450-600℃, hold at that temperature, and achieve sintering and shaping of the electrolyte sheet.

[0012] Furthermore, the process parameters for vacuum drying in step 1 are: temperature 180~200℃, vacuum degree -0.095~-0.1MPa, and time 2~4h.

[0013] Furthermore, in step 2, dry ball milling is used for mixing, or wet mixing with anhydrous ethanol is added followed by vacuum drying; when wet mixing is used, the ball-to-material ratio is 3:1 to 5:1, the ball milling speed is 40 to 100 r / min, and the ball milling time is 30 to 180 min.

[0014] Furthermore, the pressure for dry pressing in step 3 is 5–15 MPa, and the holding time is 0–30 s.

[0015] Furthermore, the stepped heating regime described in step 4 is specifically as follows: First stage: Heat at a rate of 1-5℃ / min to the temperature at which the pore-forming agent is completely decomposed, and hold for 60-90 minutes. Second stage: Increase the temperature to 450-600℃ at a heating rate of 2-3℃ / min, and hold for 10-45min; The inert atmosphere is high-purity nitrogen or argon, and the gas flow rate is 50-100 mL / min; The complete decomposition temperature of the magnesium carbonate is 480–520°C.

[0016] The beneficial effects of this invention are: 1. Strong controllability of pore structure: By adjusting the dosage and particle size of magnesium carbonate pore-forming agent, the porosity and pore size of electrolyte sheet can be precisely controlled to form continuous interconnected channels, optimize ion transport paths, effectively improve the activation speed and high-rate discharge performance of thermal battery, and reduce battery internal resistance.

[0017] 2. No impurity introduction: Magnesium carbonate is selected as the pore-forming agent, which can be completely thermally decomposed at the electrolyte sintering temperature without solid residue. The decomposition products are inert gases, with no residual impurities or carbon deposition, and will not contaminate the electrolyte system, thus ensuring the original composition ratio and electrochemical stability of the electrolyte.

[0018] 3. Balanced mechanical and electrochemical properties: The stepped heating process ensures complete decomposition of the pore-forming agent, and the slight sintering also ensures the mechanical strength of the electrolyte sheet, avoiding cracking during service and preventing excessive pore closure, thus balancing mechanical properties and ion conduction performance.

[0019] 4. Simple process and strong adaptability: The preparation process is simplified, eliminating the need for crushing and other procedures. The equipment is highly versatile, the process conditions are easy to control, and it is highly compatible with the existing industrial production system of thermal battery electrolytes, making it suitable for large-scale preparation. Attached Figure Description

[0020] Figure 1 This is the discharge curve corresponding to the porous electrolyte prepared by adding MgCO3 pore-forming agent in Example 1 of the present invention.

[0021] Figure 2This is the discharge curve of the ordinary electrolyte prepared by the conventional preparation method in Comparative Example 1 of this invention.

[0022] Figure 3 The discharge curves are for the electrolyte prepared by the method of adding magnesium carbonate pore-forming agent but not magnesium oxide adsorbent in Comparative Example 2 of this invention. Detailed Implementation

[0023] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0024] The porous thermal battery electrolyte sheet of the present invention comprises the following components: molten salt, adsorbent, and magnesium carbonate pore-forming agent, wherein the mass percentage of each component is as follows: Molten salt: 40%–60%; Adsorbent: 15%–45%; Magnesium carbonate pore-forming agent: 5%–40%; Furthermore, the molten salt is a conventional eutectic molten salt used in thermal batteries, specifically a LiCl-KCl binary eutectic molten salt, LiF-LiCl-LiBr, or LiF... LiBr KBr, LiCl LiBr KBr, LiF LiCl LiBr, LiF NaF KF and LiCl KCl The adsorbent is one of the ternary eutectic molten salts used in LiF thermal batteries; the adsorbent is one of active MgO and γ-Al2O3, and the powder particle size is controlled to be 80-200 mesh; the magnesium carbonate pore-forming agent has a particle size ≤10μm.

[0025] A solid-phase pore-forming method for preparing a porous thermal battery electrolyte sheet includes the following steps: Step 1: Raw material pretreatment Molten salt, adsorbent, and solid-phase decomposable pore-forming agent are placed in a vacuum drying oven for vacuum drying to remove adsorbed moisture and volatile impurities from the surface of the raw materials. After drying, they are transferred to a dry environment and sealed for later use.

[0026] Step 2: Powder Mixing Precisely weigh the pretreated molten salt, adsorbent, and solid-phase decomposable pore-forming agent according to the above proportions. Place the mixed powder into a ball mill for dry mixing, or add a small amount of anhydrous ethanol as a dispersion medium for wet mixing. After wet mixing, remove the dispersion medium by vacuum drying to obtain a uniformly dispersed mixed powder.

[0027] Step 3: Pressing and molding The mixed powder is added into a tableting mold and dry-pressed using a powder tableting machine. The molding pressure and holding time are controlled, and electrolyte tablets are obtained after demolding.

[0028] Step 4: Step-by-step heating sintering The electrolyte sheet is placed in a sintering furnace, an inert protective gas is introduced, and sintering is carried out using a stepped heating system. The entire process is completed under an inert atmosphere. The sintering process is divided into two stages: pore-forming agent decomposition and pore formation, and mild sintering and shaping of the electrolyte sheet, ultimately yielding a porous thermal battery electrolyte sheet.

[0029] Step 5: Cooling and discharging After sintering, maintain an inert atmosphere and cool with the furnace to room temperature. The finished electrolyte sheet is then removed.

[0030] Furthermore, the vacuum drying process parameters in step 1 are: drying temperature 180-200℃, vacuum degree -0.095~-0.1MPa, and drying time 2-4h.

[0031] Furthermore, in step 2, during wet mixing, the ball-to-material ratio is 3:1 to 5:1, the ball milling speed is 40-100 r / min, the ball milling time is 30-180 min, and the dispersion medium drying temperature is 60-80℃.

[0032] Furthermore, in step 2, the dry pressing pressure is 5-15 MPa, and the holding time is 0-30 s; preferably, the pressing pressure is 10-12 MPa.

[0033] Furthermore, in step 4, the inert protective gas is high-purity nitrogen or argon, with a gas flow rate of 50~100 mL / min; the specific process of stepped heating sintering is as follows: First stage: Heat to the temperature at which the pore-forming agent completely decomposes, at a rate of 1-5℃ / min, and hold at that temperature for 60-90 minutes to allow the pore-forming agent to fully decompose and generate gas, forming uniform and interconnected channels; Second stage: Continue heating to 450-600℃, at a rate of 2-3℃ / min, and hold at that temperature for 10-45 minutes to achieve light sintering of the electrolyte sheet, strengthen the particle bonding force, and improve the mechanical properties of the electrolyte sheet.

[0034] Furthermore, the decomposition temperature of the pore-forming agent is 480-520℃ for magnesium carbonate.

[0035] Example 1 A porous thermal battery electrolyte sheet, with the following component ratios: 50wt% LiF-LiCl-LiBr ternary eutectic molten salt, 35wt% active MgO adsorbent, and 15wt% magnesium carbonate pore-forming agent.

[0036] Preparation method: Step 1: Vacuum dry LiF-LiCl-LiBr molten salt, active MgO, and magnesium carbonate at 180℃ and -0.1MPa for 2 hours, then transfer them to a drying oven for later use. Step 2: Weigh out each powder according to the composition ratio of 500g LiF-LiCl-LiBr ternary eutectic molten salt, 350g active MgO adsorbent, and 150g magnesium carbonate pore-forming agent. Dry mix them in a ball mill with a ball-to-material ratio of 3:1, a rotation speed of 60r / min, and ball mill for 45min to obtain the mixed powder. Step 3: Add the mixed powder to the mold, hold the pressure at 10MPa for 5s, and dry press to obtain electrolyte tablets; Step 4: Place the raw sheet into a tube furnace and introduce argon gas at a flow rate of 80 mL / min; sinter according to a step system: heat from room temperature to 500℃ (3℃ / min), hold at the temperature for 60 min, heat from 500℃ to 550℃ (3℃ / min), hold at the temperature for 30 min. Step 5: Cool to room temperature in an inert atmosphere and remove to obtain a porous thermal battery electrolyte sheet.

[0037] Example 2 A porous thermal battery electrolyte sheet, with the following component ratios: 50wt% LiCl-KCl binary eutectic molten salt, 45wt% γ-Al2O3 adsorbent, and 5wt% magnesium carbonate pore-forming agent.

[0038] Preparation method: Step 1: Vacuum dry each raw material at 180℃ and -0.1MPa for 2 hours, and set aside for later use; Step 2: Weigh each powder according to the ratio of 500g LiCl-KCl binary eutectic molten salt, 450g γ-Al2O3 adsorbent, and 50g magnesium carbonate pore-forming agent. Mix them by dry ball milling for 30 minutes at a speed of 60 r / min to obtain a uniformly mixed powder. Step 3: Hold at 12MPa pressure for 5 seconds, then dry press to obtain the raw sheet; Step 4: Introduce high-purity nitrogen gas at a flow rate of 70 mL / min; Step sintering: Increase the temperature from room temperature to 480℃ (2℃ / min), hold at the temperature for 60 min, increase the temperature from 480℃ to 550℃ (3℃ / min), hold at the temperature for 10 min; Step 5: Cool the material in the furnace and discharge it to obtain porous electrolyte sheets.

[0039] Example 3 A porous thermal battery electrolyte sheet, with the following component ratios: LiF LiBr KBr ternary eutectic molten salt 45wt%, γ-Al2O3 adsorbent 15wt%, magnesium carbonate pore-forming agent 40wt%.

[0040] Preparation method: Step 1: Vacuum dry each raw material at 180℃ and -0.1MPa for 2 hours, and set aside for later use; Step 2: Press LiF LiBr Weigh out the powders in the following proportions: 450g KBr ternary eutectic molten salt, 150g γ-Al2O3 adsorbent, and 400g magnesium carbonate pore-forming agent. Mix them by dry ball milling for 50 minutes at a speed of 60 r / min to obtain a uniformly mixed powder. Step 3: Hold at 12MPa pressure for 5 seconds, then dry press to obtain the raw sheet; Step 4: Introduce high-purity nitrogen gas at a flow rate of 70 mL / min; Step sintering: Increase the temperature from room temperature to 520℃ (2℃ / min), hold at the temperature for 90 min, increase the temperature from 520℃ to 550℃ (3℃ / min), hold at the temperature for 30 min; Step 5: Cool the material in the furnace and discharge it to obtain porous electrolyte sheets.

[0041] Comparative Example 1 Electrolyte tablets without pore-forming agents, with the following component ratios: 50wt% LiF-LiCl-LiBr ternary eutectic molten salt and 50wt% active MgO adsorbent.

[0042] Preparation method: Step 1: Vacuum dry all raw materials at 180℃ and -0.1MPa for 2 hours, then transfer them to a drying oven for later use; Step 2: Weigh each powder according to the ratio of 500g LiF-LiCl-LiBr ternary eutectic molten salt and 500g active MgO adsorbent, and perform dry mixing in a ball mill with a ball-to-material ratio of 3:1, a rotation speed of 60r / min, and ball milling for 45min to obtain mixed powder. Step 3: Firing the mixed powder in a tube furnace under argon protection at a flow rate of 80 mL / min, heating from room temperature to 550℃ at a rate of 3℃ / min, and holding at the temperature for 2 hours after reaching the target temperature.

[0043] Step 4: Crush the calcined electrolyte by ball milling at a ball-to-material ratio of 3:1, a rotation speed of 60 r / min, for 60 min, and then pass it through an 80-mesh sieve to obtain electrolyte powder. Step 5: Add to the mold, hold under 10MPa pressure for 5s, and dry press to obtain electrolyte tablets.

[0044] Comparative Example 2 A porous thermal battery electrolyte sheet, with the following component ratios: 50wt% LiF-LiCl-LiBr ternary eutectic molten salt and 50wt% magnesium carbonate pore-forming agent.

[0045] Preparation method: Step 1: Vacuum dry LiF-LiCl-LiBr molten salt and magnesium carbonate at 180℃ and -0.1MPa for 2 hours, then transfer them to a drying oven for later use; Step 2: Weigh out each powder according to the composition ratio of 500g LiF-LiBr-KBr ternary eutectic molten salt and 500g magnesium carbonate pore-forming agent, and perform dry mixing in a ball mill with a ball-to-material ratio of 3:1, a rotation speed of 60r / min, and ball milling for 45min to obtain mixed powder. Step 3: Add the mixed powder to the mold, hold the pressure at 10MPa for 5s, and dry press to obtain electrolyte tablets; Step 4: Place the electrolyte sheet into a tube furnace and introduce argon gas at a flow rate of 80 mL / min; sinter according to a stepwise process: heat from room temperature to 500℃ (3℃ / min), hold at the temperature for 60 min, heat from 500℃ to 550℃ (3℃ / min), hold at the temperature for 30 min. Step 5: Cool to room temperature in an inert atmosphere and remove to obtain a porous thermal battery electrolyte sheet.

[0046] Performance test results The electrolytes prepared in Examples 1-3 and Comparative Examples 1-2 were subjected to performance tests. Porosity was measured using the Archimedes method. Molten salt leakage rate was tested by embedding the electrolyte sheet in alumina powder and holding it at 500°C for 1 hour to measure its weight change rate. Discharge performance was tested by assembling the electrolyte sheet, pressed FeS2 positive electrode, and LiB alloy negative electrode together into a single cell (54mm in diameter), with 15 cells assembled into a unit cell. The unit cell was then tested at 500°C with a discharge rate of 327 mA / cm². 2 Constant current discharge was performed at the current density, and a 35A pulse current with a pulse width of 0.1s was applied every 40s to measure the battery internal resistance. The lower operating voltage was 24V. The battery performance of each embodiment and the comparative example is shown in Table 1.

[0047] Table 1 Performance Test Table

[0048] The discharge curves of the porous electrolyte prepared in Example 1, the ordinary electrolyte prepared in Comparative Example 1, and the electrolyte prepared in Comparative Example 2 with pure magnesium carbonate pore-forming agent but without magnesium oxide adsorbent are shown below. Figure 1-3 As shown.

[0049] The battery internal resistance results for Example 1 and Comparative Example 1 are shown in Table 2.

[0050] Table 2. Battery internal resistance results for Example 1 and Comparative Examples 1-2

[0051] As shown in the table above, the electrolyte sheet prepared with the addition of magnesium carbonate pore-forming agent has a relatively high porosity. The pores inside the electrolyte can accommodate molten salt, thereby reducing the molten salt leakage rate. Simultaneously, the through-holes within the electrolyte can effectively reduce polarization, thus lowering the battery's internal resistance and increasing its capacity. However, the results of Comparative Example 2 show that excessive addition of magnesium carbonate pore-forming agent leads to excessively high electrolyte porosity. During battery activation, the molten salt needs to fully wet the pores, which increases the battery activation time and may even cause the molten salt to stop flowing within the electrolyte, thus increasing the battery's internal resistance. In Examples 1-3, the synergistic effect of magnesium carbonate pore-forming agent and magnesium oxide adsorbent allows the internal porosity of the electrolyte to be controlled within a certain range, thus reducing polarization while allowing the molten salt to quickly wet the pores. This utilizes the capillary effect to achieve rapid battery startup, achieving the best results.

[0052] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A porous thermal battery electrolyte sheet, characterized in that, The raw materials for preparing the porous thermal battery electrolyte sheet include the following components: molten salt, adsorbent, and magnesium carbonate pore-forming agent, with the following mass percentages for each component: Molten salt: 40%–60%; Adsorbent: 15%–45%; Magnesium carbonate pore-forming agent: 5%–40%; The electrolyte sheet has uniformly connected pores and channels inside; The method for preparing the porous thermal battery electrolyte sheet includes the following steps: Step 1: Vacuum dry the molten salt, adsorbent, and magnesium carbonate pore-forming agent separately; Step 2: Weigh each powder after step 1 according to the ratio, mix them evenly to obtain a mixed powder; Step 3: The mixed powder is dry-pressed into shape to obtain electrolyte tablets; Step 4: Place the electrolyte sheet in an inert atmosphere and sinter it using a stepped heating process, then cool it to room temperature to obtain a porous thermal battery electrolyte sheet. The stepped heating system includes: First stage: Heat to the temperature at which the pore-forming agent completely decomposes, so that the pore-forming agent can fully decompose and produce gas, forming uniform and interconnected pore channels; Second stage: Continue heating to 450-600℃, hold at that temperature, and achieve sintering and shaping of the electrolyte sheet.

2. The porous thermal battery electrolyte sheet according to claim 1, characterized in that, The molten salt is one of the following: LiCl-KCl binary eutectic molten salt, LiF-LiCl-LiBr ternary eutectic molten salt, LiF-LiBr-KBr ternary eutectic molten salt, LiCl-LiBr-KBr ternary eutectic molten salt, LiF-NaF-KF ternary eutectic molten salt, LiCl-KCl-LiF ternary eutectic molten salt, or LiCl-KCl-CaCl2 ternary eutectic molten salt.

3. The porous thermal battery electrolyte sheet according to claim 1, characterized in that, The adsorbent is active MgO or γ-Al2O3, and the powder particle size is 80-200 mesh.

4. The porous thermal battery electrolyte sheet according to claim 1, characterized in that, The powder particle size of the magnesium carbonate pore-forming agent is ≤10μm.

5. The porous thermal battery electrolyte sheet according to claim 1, characterized in that, The process parameters for vacuum drying in step 1 are: temperature 180~200℃, vacuum degree -0.095~-0.1MPa, and time 2~4h.

6. The porous thermal battery electrolyte sheet according to claim 1, characterized in that, In step 2, dry ball milling is used for mixing, or wet mixing with anhydrous ethanol is added followed by vacuum drying. When wet mixing is used, the ball-to-material ratio is 3:1 to 5:1, the ball milling speed is 40 to 100 r / min, and the ball milling time is 30 to 180 min.

7. The porous thermal battery electrolyte sheet according to claim 1, characterized in that, The pressure for dry pressing in step 3 is 5-15 MPa, and the holding time is 0-30 s.

8. The porous thermal battery electrolyte sheet according to claim 1, characterized in that, The stepped heating regime described in step 4 is as follows: First stage: Heat at a rate of 1-5℃ / min to the temperature at which the pore-forming agent is completely decomposed, and hold for 60-90 minutes. Second stage: Increase the temperature to 450-600℃ at a heating rate of 2-3℃ / min, and hold for 10-45min; The inert atmosphere is high-purity nitrogen or argon, and the gas flow rate is 50-100 mL / min; The complete decomposition temperature of the magnesium carbonate is 480–520°C.

Citation Information

Patent Citations

  • Preparation method of electrolyte flake for thermal battery

    CN105489910A

  • Electrolyte material for thermal battery and preparation method for electrolyte material

    CN105703002A

  • Electrolyte for thermal battery and preparation method thereof

    CN121260829A